Gastric point-of-care ultrasound (PoCUS) during pregnancy and the postpartum period: a systematic review. (November 2020) - Howle, R.; Sultan, P.; Shah, R.; Sceales, P.; Van de Putte, P.; Bampoe, S.
Highlights: PoCUS is point-of-care ultrasound. Evidence-based suggestions for using gastric PoCUS in obstetrics. Antral cross-sectional area a valid surrogate for gastric fluid volume estimation. Gastric emptying of fluid, not food, appears unaffected by term pregnancy or labour. Gastric PoCUS adds information facilitating individual aspiration risk assessment. Abstract: Personalised risk assessment of the likelihood of pulmonary aspiration is recommended for pregnant women undergoing general anaesthesia and gastric point-of-care ultrasound (PoCUS) may help to achieve this. Traditionally, risk assessment is based upon adherence to fasting times, but gastric emptying may vary during pregnancy and surgery often needs to be expedited. We systematically reviewed the evidence for gastric PoCUS up to August 2018 in pregnant and postpartum women to determine whether it can identify and quantify stomach contents, provide aspiration risk assessment via qualitative or quantitative means, and determine how gastric emptying is affected by pregnancy. Twenty-two articles comprising 1050 participants were included and studies were classified by qualitative or quantitative findings. The evidence suggests that gastric PoCUS is a reliable and feasible method of imaging the stomach in pregnancy in clinical practice. Qualitative assessment via the Perlas grading system can provide rapid assessment of gastric volume states. If fluid is visible, identification of patients at high risk of pulmonary aspiration requires measurement of antral cross-sectional area. Cut-off values of 608 mm 2 and 960 mm 2 are recommended in the semi-recumbent and right lateral semi-recumbent positions, respectively. Validated methods to quantify stomach volumes are available, however their usefulness is currently restricted to research. Gastric PoCUS also provides evidence that gastric emptying of ingested food is delayed by term pregnancy, labour and during the early postpartum period. However, the passage of fluids through the stomach appears unaffected throughout the peripartum period.